Improving machinery reliability - Bloch, Heinz P., 1933- (Houston, Tex : Gulf Pub. Co., 1998)
This totally revised, updated and expanded edition provides proven techniques and procedures that extend machinery life, reduce maintenance costs, and achieve optimum machinery reliability. This essential text clearly describes the reliability improvement and failure avoidance steps practiced by best-of-class process plants in the U.S. and Europe.
Requirements specifications. Vendor selection and bid conditioning. Machinery reliability audits and reviews. Maintenance and benchmarking reliability. Life cycle cost studies. Extending motor life in the process plant environment. Equipment reliability improvement through reduced pipe stress. Spare parts and their effect on service factor. Startup responsibilities. Maintenance for continued reliability. Maintenance cost reduction. Lubrication and reliability. Providing safety and reliability through modern sealing technology. Appendix. Index.
Includes bibliographical references and index.
Keywords: Machinery -- Reliability; Electronic books